Role of Transmembrane 4 L Six Family 1 in the Development and Progression of Cancer - Fu, Fangmei; Yang, Xudong; Zheng, Minying; Zhao, Qi; Zhang, Kexin; Li, Zugui; Zhang, Hao; Zhang, Shiwu (Frontiers in Molecular Biosciences, 2020)
Transmembrane 4 L six family 1 (TM4SF1) is a protein with four transmembrane domains that belongs to the transmembrane 4 L six family (TM4SF). Structurally, TM4SF1 consists of four transmembrane domains (TM1–4), N- and C-terminal intracellular domains, two extracellular domains, a smaller domain between TM1 and TM2, and a larger domain between TM3 and TM4. Within the cell, TM4SF1 is located at the cell surface where it transmits extracellular signals into the cytoplasm. TM4SF1 interacts with tetraspanins, integrin, receptor tyrosine kinases, and other proteins to form tetraspanin-enriched microdomains. This interaction affects the pro-migratory activity of the cells, and thus it plays important roles in the development and progression of cancer. TM4SF1 has been shown to be overexpressed in many malignant tumors, including gliomas; malignant melanomas; and liver, prostate, breast, pancreatic, bladder, colon, lung, gastric, ovarian, and thyroid cancers. TM4SF1 promotes the migration and invasion of cancer cells by inducing epithelial-mesenchymal transition, self-renewal ability, tumor angiogenesis, invadopodia formation, and regulating the related signaling pathway. TM4SF1 is an independent prognostic indicator and biomarker in several cancers. It also promotes drug resistance, which is a major cause of therapeutic failure. These characteristics make TM4SF1 an attractive target for antibody-based immunotherapy. Here, we review the many functions of TM4SF1 in malignant tumors, with the aim to understand the interaction between its expression and the biological behaviors of cancer and to supply a basis for exploring new therapeutic targets.